2003
DOI: 10.1242/dev.00650
|View full text |Cite
|
Sign up to set email alerts
|

GP130, the shared receptor for the LIF/IL6 cytokine family in the mouse,is not required for early germ cell differentiation, but is required cell-autonomously in oocytes for ovulation

Abstract: GP130 is the shared receptor for members of the IL6 family of cytokines. Members of this family have been shown to enhance the survival of migratory (E10.5) or postmigratory (E12.5) murine primordial germ cells (PGCs) in culture; however, it is uncertain what role these cytokines play during PGC development in vivo. We have examined PGC numbers in E13.5 GP130-deficient mouse embryos and found that males exhibited a slight decrease in PGC numbers; females were normal. Also, we used the Cre-loxP system to inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 29 publications
(22 reference statements)
1
49
0
Order By: Relevance
“…ablation of GP130 led to reduced gonocyte numbers in 13.5 dpc XY animals (Molyneaux et al, 2003). However, the basis for this effect was unclear, and, interestingly, these GP130-null males are fertile.…”
Section: Fgf9 As a Survival Factor In Contextmentioning
confidence: 99%
“…ablation of GP130 led to reduced gonocyte numbers in 13.5 dpc XY animals (Molyneaux et al, 2003). However, the basis for this effect was unclear, and, interestingly, these GP130-null males are fertile.…”
Section: Fgf9 As a Survival Factor In Contextmentioning
confidence: 99%
“…In previous work, using a living marker of germ cells, we have shown that germ cells leave the hindgut between E9.0 and E9.5, and migrate laterally towards each gonad (Molyneaux et al, 2001;Molyneaux et al, 2003). By E10.5, the embryos has grown significantly in size, and a mesentery has formed that displaces the hindgut from the dorsal body wall, and increases the distance of migration.…”
Section: Introductionmentioning
confidence: 94%
“…PGC isolation and reverse transcription was performed as previously described (Molyneaux et al, 2003). PGC and somatic cDNAs were diluted 1:10 and 1 µl used for PCR (25 µl).…”
Section: Rt-pcrmentioning
confidence: 99%
“…FACS with the Oct4::GFP transgene has been previously described (Heaney et al, 2009;Molyneaux et al, 2003). Briefly, gonads were digested in 0.25% trypsin (Invitrogen, Carlsbad, CA, USA) for 15 minutes at 37°C.…”
Section: Fluorescence-assisted Cell Sortingmentioning
confidence: 99%